Current insights on extracellular vesicle-mediated glioblastoma progression: Implications in drug resistance and epithelial-mesenchymal transition - Mukherjee, Swagatama; Pillai, Prakash P. (Biochimica et biophysica acta. General subjects, 2022)
Glioblastoma multiforme (GBM) is one of the most fatal tumors of the central nervous system with high rate of disease progression, diagnosis, prognosis and low survival rate. Therapeutic approaches that relied on surgical resection and chemotherapy have been unable to curb the disease progression and subsequently leading to increase in incidences of GBM reoccurrence. In the recent times, membrane-bound extracellular vesicles (EVs) have been observed as one of the key reasons for the uncontrolled growth of GBM. EVs are shown to have the potential to contribute to the disease progression via mediating drug resistance and epithelial-mesenchymal transition. The GBM-derived EVs (GDEVs) with its cargo contents act as the biological trojan horse and lead to disease progression after being received by the recipient target cells. This review article highlights the biophysical, biochemical properties of EVs, its cargo contents and its potential role in the growth and progression of GBM by altering tumour microenvironment. EVs are being explored for serving as novel disease biomarkers in a variety of cancer types such as adenocarcinoma, pancreatic cancer, color rectal cancer, gliomas and glioblastomas. Improvement in the EV isolation protocols, polymer-based separation techniques and transcriptomics, have made EVs a key diagnostic marker to unravel the progression and early GBM diagnosis. GDEVs role in tumour progression is under extensive investigations. Attempts have been also made to discuss and compare the usage of EVs as potential therapeutic targets versus existing therapies targeting drug resistance and EMT. [Display omitted] •Extracellular vesicles (EVs) mediate glioblastoma multiforme (GBM) progression via modulating the tumour microenvironment (TME).•EV-mediated epithelial-mesenchymal transition (EMT) plays a crucial role in tumorigenesis and GBM progression.•GBM-derived EVs (GDEVs) have strong implications for multi-drug resistance in GBM patients treated with known chemotherapeutic drugs.